A Multicultural Approach as a Means of Enhancing Foreign Language Training of Future Preschool and Primary Education Teachers - Savka, Iryna; Gulchenko, Svitlana (Pedagogical Discourse, 2025)
The article explores the essence of the multicultural approach as a crucial factor in enhancing the foreign language training of future preschool and primary school teachers. The purpose of the study is to substantiate the theoretical foundations and determine the pedagogical conditions for implementing a multicultural approach as a means of improving the foreign language training of future preschool and primary education teachers. In the context of contemporary professional education, it is increasingly important for teachers to develop the ability to engage in effective intercultural communication, demonstrate tolerance, respect cultural diversity, and be prepared to work in a globalized educational environment. The study analyzes the theoretical foundations of multicultural education, highlighting its relevance and practical integration into foreign language instruction. Particular attention is given to the pedagogical conditions, methods, and tools necessary for implementing a multicultural approach in language learning, including the use of interactive and multimedia resources, culturally authentic materials, and experiential activities that promote cultural awareness. The article argues that the systematic incorporation of multicultural principles not only fosters the development of foreign language communicative competence but also contributes to the formation of essential personal and professional qualities such as empathy, adaptability, critical thinking, and reflective practice. Furthermore, the research emphasizes that multicultural education equips future teachers with the skills to create inclusive and culturally responsive learning environments, thereby preparing them to meet the demands of modern educational systems and diverse classrooms. Overall, the multicultural approach is presented as an effective means of enriching teacher preparation programs and supporting the holistic development of both professional and intercultural competencies in emerging educators.